Specificity of peer difficulties to social anxiety in early adolescence: categorical and dimensional analyses with clinical and community samples. Issue 6 (2nd November 2017) - Early, Martha C.; Biggs, Bridget K.; Makanui, Kalani P.; Legerski, John Paul; Van Allen, Jason; Elledge, Allison R.; Whiteside, Stephen P.
ABSTRACT: Background and Objectives: We investigated the specificity of social difficulties to social anxiety by testing associations of social anxiety and other anxiety presentations with peer acceptance and victimization in community and treatment-seeking samples of adolescents aged 12–14 years. Design: Cross-sectional, quantitative survey. Methods: Adolescents from the community ( n  = 116) and a clinical setting ( n  = 154) completed ratings of anxiety symptoms, perceived social acceptance, and peer victimization. Their parents also completed ratings of the adolescents' anxiety and social acceptance. Results: Social acceptance was lowest among adolescents with social anxiety disorder (SAD) and lower among adolescents with other anxiety disorders than in the community sample. Anxiety symptoms were negatively correlated with social acceptance, but these associations were not unique to social anxiety symptoms. Girls in the community sample reported more overt victimization than girls with SAD and with other anxiety diagnoses. Relational victimization was associated with social and nonsocial anxiety symptoms only in the community sample. Conclusions: Our findings supplement recent laboratory-based observational studies on social functioning among adolescents with SAD and other anxiety disorders. Although social anxiety may be associated with unique social skill deficits and impairment, concerns about peer relations should also be considered among adolescents with other anxiety symptoms.